INVESTIGATING TEACHERS’ STRATEGIES IN TEACHING VOCABULARY - Trisna Kurniawati; Rifiqoh Rifiqoh; Wahyudin Wahyudin (Tadulako University, 2022)
The purposes of the research are two folds: to find out the vocabulary teaching strategies used by the English teachers at SMP Negeri 6 Palu, and to identify the reasons of implementing the strategies in the classroom. This research used qualitative research design. The participants of this research were three English teachers. In collecting the data, the instruments used were observation and interview. The data were analyzed by using descriptive analysis. The findings showed that there were some teaching strategies used by the teachers in teaching vocabulary. The strategies used by the English teachers in teaching vocabulary were: (1) the use of game like guessing game and dictation (by relying on learning topic), (2) reading textbook, (3) translation (by looking up dictionary), and (4) asking question. The main reason of implementing teaching strategies was, they wanted to make the students active in the class. The basic consideration as an active facilitator in choosing the teaching strategies was to make classroom atmosphere that can make the students interact freely with each other in achieving learning goals